Transcutaneous migration of foreign body into thorax in children: A report of two cases - Bothra Jyoti; A. Narendra Kumar; Jayaram Harish (Elsevier, 2016)
Inhalation and ingestion of foreign bodies is common in pediatric age group. However transcutaneous migration of sharps into the lung parenchyma is rarely reported and can be hazardous. We report two such cases with details on the diagnosis and the treatment modalities used for the management.